Application of Electrical Capacitance Tomography on single-plane sensor measurement - Shafquet, A. (2013)
Electrical Capacitance Tomography (ECT) is a non-intrusive type of Process Tomography, which is used for obtaining information about the distribution of the contents of closed pipes by measuring variations in the dielectric properties of the material inside the vessel. The customary approach separates the two-phases first and then measures the mixture as individual components that results in the disruption of incessant industrial processes. Due to these limitations, this study is aimed to analyze a non-invasive, experimental study by using Electrical Capacitance Tomography (ECT). This paper presents the series of imaging experiments for waxy crude oil using a single-plane ECT sensor by variation in temperature. Normally in calibration, it is necessary to remove the sensor from transportation line and measure the capacitances when filled with the measured medium. On varying the temperature, different flow images were observed. FEM simulation was also performed to obtain the capacitance values. The raw data obtained from ECT tomogram images were analyzed utilizing distribution models and simulations using COMSOL. The result shows that ECT measurements are dependent on calibration method performed as well as the relative permittivity of the material being used for the sensor. Â© 2013 IEEE.